Differential roles of ERRFI1 in EGFR and AKT pathway regulation affect cancer proliferation. (15th January 2018) - Cairns, Junmei; Fridley, Brooke L; Jenkins, Gregory D; Zhuang, Yongxian; Yu, Jia; Wang, Liewei
Abstract: AKT signaling is modulated by a complex network of regulatory proteins and is commonly deregulated in cancer. Here, we present a dual mechanism of AKT regulation by the ERBB receptor feedback inhibitor 1 (ERRFI1). We show that in cells expressing high levels of EGFR, ERRF1 inhibits growth and enhances responses to chemotherapy. This is mediated in part through the negative regulation of AKT signaling by direct ERRFI1‐dependent inhibition of EGFR. In cells expressing low levels of EGFR, ERRFI1 positively modulates AKT signaling by interfering with the interaction of the inactivating phosphatase PHLPP with AKT, thereby promoting cell growth and chemotherapy desensitization. These observations broaden our understanding of chemotherapy response and have important implications for the selection of targeted therapies in a cell context‐dependent manner. EGFR inhibition can only sensitize EGFR‐high cells for chemotherapy, while AKT inhibition increases chemosensitivity in EGFR‐low cells. By understanding these mechanisms, we can take advantage of the cellular context to individualize antineoplastic therapy. Finally, our data also suggest targeting of EFFRI1 in EGFR‐low cancer as a promising therapeutic approach. Synopsis: The ERBB receptor inhibitor ERRFI1 regulates AKT/EGFR signaling in an EGFR‐dependent manner. In EGFR‐low cells, ERRFI1 activates AKT by blocking the PHLPP‐AKT interaction. In EGFR‐high cells, ERRFI1 functions as a negative regulator of the EGFR pathway. In EGFR‐low cells, ERRFI1 activates AKT and promotes proliferation and chemotherapy resistance. In EGFR‐low cells, AKT inhibition is beneficial and increases chemosensitivity. In EGFR‐high cells, reduced ERRFI1 leads to active EGFR and increased cell proliferation. In EGFR‐high cells, EGFR inhibition is beneficial and sensitizes for chemotherapy. Abstract : The ERBB receptor inhibitor ERRFI1 regulates AKT/EGFR signaling in an EGFR‐dependent manner. In EGFR‐low cells, ERRFI1 activates AKT by blocking the PHLPP‐AKT interaction. In EGFR‐high cells, ERRFI1 functions as a negative regulator of the EGFR pathway.